2012
DOI: 10.1371/journal.pone.0039234
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Is Associated with Erectile Dysfunction: A Cross-Sectional Study in Chinese Men

Abstract: Background Testosterone is essential for the regulation of erectile physiology, but the relationship between low testosterone and erectile dysfunction (ED) has not been firmly established. Purpose To examine the association between serum total, free and bio-available testosterone and ED in a population-based sample. Methods A consecutive series of 1776 men aged 20–77 participated in the routine physical examination from September 2009 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 46 publications
3
37
1
1
Order By: Relevance
“…Low levels of free testosterone have been associated with ED [27][28][29]. Contrary to our expectations, the free testosterone levels were not associated with IIEF scores after correcting for confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Low levels of free testosterone have been associated with ED [27][28][29]. Contrary to our expectations, the free testosterone levels were not associated with IIEF scores after correcting for confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Low testosterone, HOMA-IR, and age were predictors of ED in our study group. A study from China confirmed the role of testosterone in ED [32]. Testosterone deficiency has been blamed for worse cardiometabolic profile [33].…”
Section: Discussionmentioning
confidence: 99%
“…MetS was defined based upon the updated the Adult Treatment Panel III of the National Cholesterol Education Program (NCEP-ATPIII) for Asian-Americans [34], which recognizes the existence of MetS if any 3 or more of the following 5 components are present: 1. Abdominal obesity: waist circumference ≥ 90 cm in men or ≥ 80 cm in women; 2.…”
Section: Methodsmentioning
confidence: 99%